Uncomplicated malaria in children: The place of rapid diagnostic test - Elechi, Hassan Abdullahi (Niger Med J, 2015)
BACKGROUND: Malaria has remained a major cause of morbidity and mortality among the under-five children in Nigeria. Prompt and accurate diagnosis of malaria is necessary in controlling this high burden and preventing unnecessary use of anti-malarial drugs. Malaria rapid diagnostic test (MRDT) offers the hope of achieving this goal. However, the performance of these kits among the most vulnerable age group to malaria is inadequate. MATERIALS AND METHODS: In this cross-sectional study, 433 out-patients, aged <5 years with fever or history of fever were enrolled. Each candidate was tested for malaria parasitaemia using ACON; malaria pf. Thick and thin films were also prepared from the same finger prick blood for each candidate. RESULT: Malaria rapid diagnostic test had sensitivity of 8.3%, specificity of 100%, positive predictive value (PPV) of 100% and negative predictive value (NPV) of 74%. The sensitivity of MRDT increased with increasing age. This effect of age on sensitivity was statistically significant (P = 0.007). Similarly parasite density had significant effect on the sensitivity of MRDT (P = <0.001). CONCLUSION: Histidine-rich protein-2 based MRDT is not a reliable mean of diagnosing malaria in the under-five age children with acute uncomplicated malaria.